Low risk of relapse and deformity among leprosy patients who completed multi-drug therapy regimen from 2005 to 2010: A cohort study from four districts in South India. - Prabu Rajkumar; Girish Kumar Chethrapilly Purushothaman; Manickam Ponnaiah; Devika Shanmugasundaram; Jayasree Padma; Rang Lal Meena; Selvaraj Vadivoo; Sanjay M Mehendale (PLoS Neglected Tropical Diseases, 2021)
Introduction Relapse of leprosy among patients released from treatment (RFT) is an indicator of the success of anti-leprosy treatment. Due to inadequate follow-up, relapse in leprosy patients after RFT is not systematically documented in India. Relapsed leprosy patients pose a risk in the transmission of leprosy bacilli. We determined the incidence of relapse and deformity among the patients RFT from the leprosy control programme in four districts in South India. Methods We conducted two follow-up surveys in 2012 and 2014 among the leprosy patients RFT between 2005 and 2010. We assessed them for any symptoms or signs of relapse, persistence and deformity. We collected slit skin samples (SSS) for smear examination. We calculated overall incidence of relapse and deformity per 1000 person-years (PY) with 95% confidence intervals (CI) and cumulative risk of relapse. Results Overall, we identified 69 relapse events, 58 and 11, during the first and second follow-up surveys, respectively. The incidence of relapse was 5.42 per 1000 PY, which declined over the years after RFT. The cumulative risk of relapse was 2.24%. The rate of deformity among the relapsed patients was 30.9%. The overall incidence of deformity was 1.65 per 1000 person years. The duration of M. leprae detection in smears ranged between 2.38 and 7.67 years. Conclusions Low relapse and deformity rates in leprosy RFT patients are indicative of treatment effectiveness. However, a higher proportion of detection of deformity among relapsed cases is a cause for concern. Periodic follow-up of RFT patients for up to 3 years to detect relapses early and ensure appropriate treatment will minimize the development of deformity among relapsed patients.